Microparticle - based platform for point-of-care immunoassays - Teppo Salminen; Etvi Juntunen; Merja Lahdenranta; Iida Martiskainen; Sheikh M. Talha; Kim Pettersson (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2022)
There is a need for quantitative and sensitive, yet simple point-of-care immunoassays: We have developed a point-of-care microparticle-based immunoassay platform which combines the performance of a microliter well based assay with the usability of a rapid assay. The platform contained a separate reaction and detection chambers and microparticles for the solid-phase. Photoluminescent up-converting nanoparticles (UCNPs) were used as labels. The platform was tested with a cardiac troponin I assay, and a limit of detection of 19.7 ng/L was obtained. This study demonstrates the feasibility of developing point-of-care assays on the new platform for various analytes of interests.